APLIKASI PUPUK DAN MULSA JERAMI PADA TANAMAN KEDELAI TERHADAP SERANGAN HAMA DAN PRODUKSI - Rimbing, J.; Pelealu, J.; Sualang, D. (Universitas Sam Ratulangi, 2015)
ABSTRACT The research was arranged in a randomized block design (RBD), with 10 treatments and 3 replications. To get the active insects pests, net sweepings were done for the flying insects, while other pests were observed directly on the plants. Collecting data of plant damages were made by systematic diagonal lines, except for viruses, census was conducted on each experimental plot. The results of this experiment documented 12 species of insect pests attacking soybean plants. Soybean pest populations were relatively low, except for Aphis glycine that was quite high. In all treatments, plant damage caused by sucking pest Piezodorus sp and Riptortus linearis were relatively low of 1.53 % to 1.94 %; it indicated an insignificant effect to decline the production. Crop damages by virus showed a significant effect. The lowest virus attacks found on compost of 5 tons per ha with 43 plants infected per treatment, the highest virus attack showed on combination of 5 tons compost per ha + inorganic fertilizer + mulch, in which there were 274 infected plants per treatment. Apparently virus attacks gave impact on soybean production. The highest production were documented on treatment of 5 tons compost per ha with production of 0.55 tons per ha, while the lowest production was found on combination of 5 tons compost per ha + inorganic fertilizer + mulch, in which the production was 0.22 tons per ha. Keywords: fertilizer, mulch, insect pest, production